Increased Protein with Decreased Carbohydrate Intake Reduces Postprandial Blood Glucose Levels in Women with Gestational Diabetes: The iPRO Study - Kimberly K. Trout; Charlene W. Compher; Cara Dolin; Carrie Burns; Ryan Quinn; Celeste Durnwald (Mary Ann Liebert, 2022)
Introduction: There is an urgent need to establish an evidence base for recommendations regarding proportions of macronutrients for optimized nutritional management of gestational diabetes mellitus (GDM). Our study compared isocaloric diets in women with GDM that differed in protein and carbohydrate content with fats held constant. We hypothesized that the glucose area under the curve (AUC) would be lower with the higher protein/lower carbohydrate diet. Research Design and Methods: This study used a random order crossover design within a controlled research unit environment. Nineteen women were randomized to treatment, with 12 participants completing both arms of the study. Blood sampling occurred preprandially and at t?=?30, 60, 120, and 180" relative to meals. Inclusion criteria were confirmed diet-controlled GDMA1, singleton gestation, and with no pre-existing medical comorbidities. Mean gestational age at entrance to study?=?32 (?1.76) weeks. Mean prepregnant body mass index of participants?=?28.7 (?5.3) kg/m2 Participants were randomly assigned initially to either an increased protein/low carbohydrate (iPRO30%/CHO35%) diet or a lower protein/higher carbohydrate (LPRO15%/CHO50%) diet for a 36 hour inpatient stay on the research unit. All meals and snacks were prepared in a metabolic kitchen. After a 3?7 day washout period, participants were randomized to the opposite treatment. Results: On day 2 (with confirmed overnight fasting), the average 3-hour pre- through postprandial glucose AUC was lower in iPRO30%/CHO35% treatment arm (17395.20???2493.47 vs. 19172.47???3484.31, p?=?0.01). Conclusion: This study is the first to demonstrate that a higher protein, lower carbohydrate meal, especially at breakfast, can result in lower postprandial blood glucose values in women with gestational diabetes. A lack of statistically significant differences at other collection time points could have been due to several factors, but most likely due to small sample size. Longer term outcomes of a higher protein diet, including maternal glycemic control, nitrogen balance, and impact on fetal growth outcomes, are needed.